EFFECT OF CoCu MEDICA, HIT RIT AND PLACENTREX ON SERUM BIOCHEMICAL PROFILE OF ANESTRUS COWS - AZAD, C S; SINGH, M P; SINGH, BALRAJ; SINHA, M P; SHARMA, D K (The Indian Journal of Animal Reproduction, 2010)
A total number of 40 crossbred anestrus cows were randomly !located to four groups viz Gr I (CoCu Medica), Gr. II (HitRit), Gr. Ill (Placentrex) and Gr. IV (Control). Serum biochemical profiles namely glucose, total protein, calcium, phosphorus, copper and iron were estimated which increased significantly (P<0.01) in all the treatment groups on the day of onset of estrus.